The geoepidemiology of immune thrombocytopenic purpura - Deane, Sean; Teuber, Suzanne S.; Gershwin, M. Eric (Autoimmunity reviews, 2010)
First described in 1735 (Watson-Williams et al., 1958 [1]), immune-mediated platelet destruction is a phenomenon of protean associations that has historically varied in its definition. Recently, consensus guidelines were proposed for a standardized system of nomenclature that preserves the acronym “ITP” but encompasses a number of causes of immune-mediated thrombocytopenias, including both primary immune thrombocytopenia as well as such entities as thrombocytopenia associated with connective tissue diseases or cancer. In this paper, we will focus on current aspects of geoepidemiology, pathophysiology, diagnosis and management of adult and pediatric primary immune thrombocytopenia. It is clear that both genetic and extrinsic factors exist for ITP and are likely different between children and adults. Immune thrombocytopenia remains a challenging problem but our understanding of its pathophysiology has greatly improved.